510 THE DEFENSIVE WITHDRAWAL MECHANISM OF RETETEREBELLA QUEENSLANDIA AND SPIROBRANCHUS GIGANTEUS: STIMULATION THRESHOLD AND REFRACTORY PERIODS. (1st January 2006) - Dugan, J. A.; Curd, E.; Hall, C.
Abstract : Stimulatory behavior represents a primary physiological response. Analysis of the defensive retraction of Reteterebella queenslandia's tentacles and Spirobranchus giganteus's branchial crowns reveals a dynamic relationship between energy requirement and appendage jeopardy. The time that elapses before organisms re-emerge their appendages to the environment has been termed the refractory period. To induce the defensive mechanism of these species an intensified progression of stimulation was applied until retraction of all exposed appendages occurred. The type of stimulus administered to R. queenslandia involved the use of a slight brush of water over a single tentacle, followed by a touch with a finger and finally a pinch. A wave of the hand over progressively shorter distances toward S. giganteus elicited a defensive response. The type of stimulus required to induce the withdrawal did not change in intensity over the course of the four trials, indicating that a certain threshold must be administered. The refractory periods obtained for S. giganteus revealed a slightly increasing trend though statistically insignificant, as since the organism depends on its branchial crowns for respiration in addition to prey capture, it would not want to jeopardize such multifunctional structures. R. queenslandia, whose tentacles serve only for prey capture, did display significantly lower refractory periods as the trials progressed, suggesting its requirement for food outweighs the cost of an environment prone to constant stimulation.